Adiponectin Regulates the Development and Progression of MCA-Induced Sarcoma in Mice - Rongxin Zhang; Kai Zhang; Xi Wu; Zhihui Zhang; Shuyu Fu; Yurong Da; Mei Mei; Qi Zhang; Yan Li; Zhenyi Xue; Lijuan Zhang; Peng Zhao (International Journal of Immunotherapy and Cancer Research - Peertechz Publications, 2015)
Background: Sarcomas are malignant tumors with low survival rates and remain refractory to the current therapeutic methods. Adiponectin plays crucial roles in many physiological responses. Studies have shown that adiponectin could regulate various tumors. However, the roles of adiponectin in sarcomas remain unknown. Results: In this study, we found that the adiponectin-deficient mice induced by MCA develop sarcomas more rapidly and frequently than the WT mice do. With the sarcomas formation, adiponectin deficiency showed inhibiting effect on tumor growth and reduced the mortality rates of the mice with sarcomas. Conclusions: Adiponectin inhibits the sarcomas formation, but may promote the growth of tumor after sarcomas occur.